2012
DOI: 10.3762/bjoc.8.225
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of bisallenes

Abstract: SummaryThis review describes the preparation, structural properties and the use of bisallenes in organic synthesis for the first time. All classes of compounds containing at least two allene moieties are considered, starting from simple conjugated bisallenes and ending with allenes in which the two cumulenic units are connected by complex polycyclic ring systems, heteroatoms and/or heteroatom-containing tethers. Preparatively the bisallenes are especially useful in isomerization and cycloaddition reactions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 290 publications
(325 reference statements)
0
21
0
Order By: Relevance
“…Taken together, these studies show that conjugated bisallenes [39], which are readily available by high-yielding synthetic transformations from simple substrates, are useful starting materials for the preparation of a plethora of novel organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these studies show that conjugated bisallenes [39], which are readily available by high-yielding synthetic transformations from simple substrates, are useful starting materials for the preparation of a plethora of novel organic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…25,55 Although no X-ray analysis of 6 has been reported (the compound is a liquid at room temperature), X-ray structural analyses of about 4 dozen solid derivatives of 6 have been reported in the Cambridge Crystallographic Database. 16 Turning to Diels-Alder cycloadditions now, while we have been unable to locate a publication describing the experimental or computed conformational dynamics of the molecule, it is clear that 6 has no difficulties acquiring the cisoid conformation required for the reaction to take place. As mentioned earlier, calculations point to a faster and more thermodynamically favorable Diels-Alder reaction with 6 as a diene than with vinylallene 4.…”
Section: Special Topic Synthesis 22 Bisallenesmentioning
confidence: 97%
“…Cycloallenes are synthetically interesting compounds that, given their reduced symmetry due to the ring structure, exhibit helical MOs. 29,30,[71][72][73][74][75] Most recently, Ramirez et al 30 demonstrated that secondary orbital interactions due to the helical frontier MO topology are responsible for the endo selectivity in Diels-Alder reactions. Four molecular structures of simple cycloallenes are shown in the top of Figure 7, from left to right, 1,2cyclohexadiene, 1,2-cycloheptadiene, 1,2-cyclooctadiene and 1,2-cyclononadiene.…”
Section: Cycloallenesmentioning
confidence: 99%